Environmental performance assessment in a company of the ceramic industry in Tocantins - Silva, Núbia Adriane da; Furtado, Octaviano Sidnei; Dias, Willian de Souza; Sellitto, Miguel Afonso (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This paper aims to use the SBP method to verify the environmental performance of a company in ceramic industry, identifying their potential for improvement. After a semi-structured interview was carried out a content analysis, confronted with the literature. Measurement indicators were organized into five constructs: atmospheric emissions; Liquid effluents; Solid waste; Use of resources; and management and compliance. The results show that the company has an environmental performance of 73, with 27 of margin for improvement. The construct with greater scope for improvement is resource use, followed by solid waste. The company’s improvement efforts should focus on actions that improve the indicators of these two constructs.